Pengambilan Keputusan Dalam Pemilihan Supplier Dengan Metode Analytical Hierarchy Process (AHP) dan Technique For Others Reference by Similarity to Ideal Solution (TOPSIS) - Wicaksono, Martin; Fathimahhayati, Lina Dianati; Sukmono, Yudi (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2020)
M-Merchandise is a business launched by the Mulawarman University Business Management Agency. The problem for these merchandise products is that in determining suppliers it has not been done well, there is no particular method of determining suppliers. So M-Merchandise needs to do supplier selection to get the best supplierr. In making a decision, determining suppliers is applied to the AHP and TOPSIS methods. The AHP method is used to determine the most influential criteria with a paired comparison matrix, then the weight values ​​are used as input to the TOPSIS method to rank suppliers. From the results of the AHP calculation, M-Merchandise have obtained the quality criteria with the highest weight of 0.300. This shows that quality is a major factor in supplier selection. Furthermore, other criteria applied are price with a weight of 0.221, shipping 0.040, technical capability 0.165, a communication system 0.095, and a packaging ability 0.179. From the results of the TOPSIS calculation, the PK supplier is the best supplier to choose with a value of 0.617